Business Charity Movement of Aisyiyah Organization West Sumatra in 1968-2016 - Sahputra, Siir (International Journal of Research in Education, 2024)
This article discussed the Aisyiyah group and the women's movement in West Sumatra from 1968 to 2016. Byutilizing a historical method that includes historiography, source critique, interpretation, and heuristic stages. According to the study's findings, the Aisyiyah Organization was initially founded in Yogyakarta and formed its Batang River branch. Prior to 1968, this Organization's branches and branches quickly expanded in a number of West Sumatra locales, including Padang Panjang, Bukittinggi, Simabur, Payakumbuh, and Pesisir Selatan. After 1968 the Aisyiyah organization was spread across 18 regencies and cities in West Sumatra. The Aisyiyah Organization movement is no longer in the form of resistance as in the previous colonial era, but in the form of awareness to catch up with women in the field of charity and business such as in the fields of education, health, social welfare and the economy. Aisyiyah's charitable business movement includes a number of initiatives, such as sending as many young children as possible to ABA Kindergartens and establishing a Teacher Education School (SPG) to support educated teachers, expanding Aisyiyah Islamic clinics as places for women to seek treatment and supporting Schools Health Nurses as educated midwives, and empowering girls to enroll in Aisyiyah.